2007
DOI: 10.1128/jvi.02750-06
|View full text |Cite
|
Sign up to set email alerts
|

Ultracentrifugation of Serum Samples Allows Detection of Hepatitis C Virus RNA in Patients with Occult Hepatitis C

Abstract: Occult hepatitis C virus (HCV) infection of patients with abnormal liver function tests of unknown originwho are anti-HCV and serum HCV RNA negative but who have HCV RNA in the liver has been described. As HCV replicates in the liver cells of these patients, it could be that the amount of circulating viral particles is under the detection limit of the most sensitive techniques. To prove this hypothesis, serum samples from 106 patients with occult HCV infection were analyzed. Two milliliters of serum was ultrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 24 publications
2
105
0
3
Order By: Relevance
“…Primers and conditions of this strand-specific realtime PCR have been reported. 13 The fluorescence resonance energy transfer probes used were described by Bullock et al 14 These allow discrimination between HCV genotypes 1, 2, 3, and 4 by melting-curve analysis. Quantification of both HCV-RNA strands was performed using two standard curves constructed with 10-fold dilutions of synthetic genomic and antigenomic HCV-RNA (from 3.2 ϫ 10 8 to 0.32 copies).…”
Section: Concise Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers and conditions of this strand-specific realtime PCR have been reported. 13 The fluorescence resonance energy transfer probes used were described by Bullock et al 14 These allow discrimination between HCV genotypes 1, 2, 3, and 4 by melting-curve analysis. Quantification of both HCV-RNA strands was performed using two standard curves constructed with 10-fold dilutions of synthetic genomic and antigenomic HCV-RNA (from 3.2 ϫ 10 8 to 0.32 copies).…”
Section: Concise Methodsmentioning
confidence: 99%
“…This assay was capable of detecting 3.2 molecules of the correct strand while unspecifically detecting 10 7 to 10 8 copies of the incorrect strand. 13 For ensuring the specificity of the results, HCV-RNA detection was performed blindly on different days by two different operators. In addition to PBMC from the 10 healthy anti-HCV negative patients, total RNA isolated from HepG2 cells and blanks were used as negative controls.…”
Section: Concise Methodsmentioning
confidence: 99%
“…It has been proposed that the number of circulating viral particles is too low to be detected by conventional molecular techniques. 5 Although several authors have described this new form of infection with emerging implications in different clinical scenarios, 6 few data are available in the setting of liver transplantation.…”
Section: When To Search For Occult Infection After Eradication Of Hepmentioning
confidence: 99%
“…All these specimens may well represent true HCV RNA-positive samples in which viral breakthrough was serendipitously identified; however, the supporting evidence is lacking. Additionally, the authors should have tested liver biopsy material to support the supposition made in the article title.The existence of seropositive and seronegative aviremic occult HCV has been proposed by Carreno et al [3][4][5] These patients often have periodic elevations of alanine aminotransferase. Hoare et al 1 reported that 15.2% of the study group had alanine aminotransferase elevations; perhaps these latter individuals would have been a more appropriate study group.…”
mentioning
confidence: 99%
“…The existence of seropositive and seronegative aviremic occult HCV has been proposed by Carreno et al [3][4][5] These patients often have periodic elevations of alanine aminotransferase. Hoare et al 1 reported that 15.2% of the study group had alanine aminotransferase elevations; perhaps these latter individuals would have been a more appropriate study group.…”
mentioning
confidence: 99%